PENINGKATAN PROSES DAN HASIL BELAJAR TEMATIK DENGAN MENGGUNAKAN MODEL PICTURE AND PICTURE DI KELAS V SD NEGERI 218/II LIMBUR BARU - Martinis; Abdulah (Jurnal Muara Olahraga, 2024)
ABSTRACT Based on observations at SD Negeri 218 Limbur, the learning outcomes of class V students are still relatively low. This can be seen from the minimum completion criteria (KKTP) set by the school of 75, out of 23 students, only 12 students have completed their studies and 11 other students have not yet completed their studies. Student learning outcomes are still low because the learning used still uses conventional methods (lectures). This method makes students passive and less creative, so it is necessary to use a learning model that can make students more active and interested in learning. A model that can be applied is, for example, using the Picture and Picture learning model. The aim of this research is to improve student learning outcomes in thematic subject material on natural events that occur in Indonesia and their impact on living things and the environment by using the Picture and Picture model for class V students at SD Negeri 218 Limbur first semester 2023/2024 academic year Type The research used was Classroom Action Research (PTK) which consisted of 2 cycles with the research subjects being class V students with the Competency Standard "Understanding changes that occur in nature and their relationship with the use of natural resources" at SD Negeri 218 Limbur. The research results show that the use of the Picture and Picture learning model can improve student learning outcomes. In cycle I, an average score of 81 was obtained with a completion percentage of 78% and this increased in cycle II with an average score of 89 with a completion percentage of 96%. From the results of this research it can be concluded that the use of the Picture and Picture learning model can improve thematic learning outcomes of class V students at SD Negeri 218 Limbur. Keywords : Picture and Picture , Learning Results, Learning Process, Thematic.